Race, Religion, and the Scottish Empire: St. Andrew’s Kirk, Nassau, ca. 1810-1852 - Jones, Andrew Michael (International Journal of Bahamian Studies, 2020)
This article examines the relationships between the Scottish diaspora community and the Afro-Caribbean and Anglican populations of New Providence Island during the first half of the 19th century. St. Andrew’s Kirk in Nassau was founded by Scottish emigrants in 1809 to provide them with a Presbyterian place of worship. The original members were, in part, British Loyalists – formerly based in North America – who had accepted Royal land grants on the archipelago in 1783. Many brought enslaved people with them, expecting their fortunes to recover in a new plantation economy. In 1837 William Maclure, a native of Ayrshire in southwest Scotland, became the fifth minister appointed to the Kirk. Unlike the previous ministers, Maclure remained in his Bahamian pulpit for over 25 years. Sources from his tenure at the church provide a window into the social, racial, and theological dynamics of Victorian New Providence. For example, in a letter published in a Scottish newspaper in the late autumn of 1852, Maclure stated somewhat cryptically that “the remains of the curse of slavery are upon us.” This article will offer an answer to the following three questions: First, to what degree have recent studies of the Scottish diaspora communities in the British West Indies underappreciated the Bahamian situation? Second, how did the members and ministers of St. Andrew’s Kirk, Nassau interact with issues of race and slavery from the founding of the church to the era in which Maclure’s letter was published? Lastly, what exactly was William Maclure referring to regarding the “curse of slavery”?